Efficacy of disinfectant-impregnated wipes used for surface disinfection in hospitals: a review - Xinyu Song (2019)
Background “Ready-to-use” disinfecting wipes (also known as pre-impregnated disinfecting wipe) are broadly used in food industry and domestic situations. Their application in hospitals and healthcare centres for decontamination of medical devices and surfaces is steadily increasing because of their convenient implementation in practice and reliable performance. Beside their acceptable compliance and easy application, literature reported the disinfection failure due to the interaction between textile substrate and active ingredients, which can highly increase the risk of an infection outbreak. This review aims to call attention to the wide range of variables affecting the disinfectant-impregnated wipes’ (DIWs) disinfection performances in hospitals. Methods A systematic literature search based on the five categories i. wipes, ii. disinfectants, iii. application methods, iv. interaction between wipes and active ingredients and v. wiping strategy which can possibly influence the disinfection effectiveness of DIWs was conducted by Google scholar. Studies regarding the efficacy evaluation of DIWs in clinical applications were also reviewed from the National Centre for Biotechnology Information database. Results Variables that impact on the disinfection performance of disinfectant-impregnated wipes in surface disinfection in hospitals were summarised and critically discussed. In addition to the information, current disinfectant-impregnated wipes’ decontamination efficacy test standards were reviewed, and different standards exposed some disadvantage in their testing design. Conclusion Various parameters contribute to the impact of DIWs disinfection performance in practice. The interaction between disinfectant active ingredients and the wiping materials barricades their broad application in hospitals. More studies of the DIWs’ disinfection efficacy in clinical practice are in need. Current standards evaluating the DIWs’ efficacy are required to improve for more realistic condition simulation and differentiating between mechanical removal of inoculum from a surface and chemical inactivation of the test microbe.